Kajian Ayat-Ayat Syifa dalam Perspektif Tafsir dan Implementasinya dalam Pengobatan Ruqyah - Sismanto; Tutik Hamidah (Studia Quranika, 2022)
This research used qualitative phenomenology. The data were collected by interview and documentary techniques. Determination of informants using purposive sampling consisting of the chairman, secretary, and practitioner members who are members of Jam’iyah Ruqyah Aswaja (JRA). The data obtained was analyzed directly and interpreted by the stages of presenting text, messages, instructions, and information. The research results reveal that; (1) there are six syifa verses contained in the Qur'an that can heal people who are sick. The syifa verses are found in the Quran letter At-Taubah (9) :14, Fussilat (41): 44, Yunus (10) :57, An-Nahl (16) : 69, Al-Israa (17): 82, and Asy-Syu'araa (26): 80, (2) Hadith and atsar friends related to the syifa verses contained in the hadith of the book of Bukhari number 5301 and 5309. Based on the path of transmission, the two traditions are agreed to be true traditions even though in the text there are differences but in meaning it has the same substance and (3) Treatment of ruqyah using syifa verses is carried out by reciting verses of the Quran and blowing it to the patient and through the medium of water.